First g factor measurement using a radioactive $^{76}$Kr beam - Kumbartzki, G.; Cooper, J.R.; Benczer-Koller, N.; Hiles, K.; Mertzimekis, T. J.; Taylor, M.J.; Speidel, K.-H.; Maier-Komor, P.; Bernstein, L.; McMahan, M.A.; Phair, L.; Powell, J.; et al. (Phys. Lett. B, 2004)
The g factor of the first 2+ state of radioactive 76Kr (T1/2=14.8 h) has been measured, extending the systematics of the previously measured stable 78,80,82,84,86Kr isotopes. The measurement was performed with a radioactive 76Kr ion beam applying projectile Coulomb excitation in inverse kinematics combined with the transient magnetic field technique. The 76Kr beam was produced and accelerated in batch mode (re-cyclotron method) at the Lawrence Berkeley National Laboratory 88-Inch Cyclotron. A total of three production and acceleration cycles yielded six hours of beam on target with peak rates of 108 particles/s. About 5.6×104 particle-? coincidence events were recorded. The g factor g(76Kr;2 +1)=+0.37(11) was obtained by direct comparison to the known g(78Kr;2+1) value re-measured immediately after the 76Kr runs with the same setup and under almost identical kinematic conditions. © 2004 Elsevier B.V. All rights reserved.
Keywords: 21.10.Ky; 25.70.De; 27.50.+e; article; Coulomb excitation; cyclotron; Inverse kinematics; isotope; Kinematics; Krypton; magnetic field; Magnetic moment; mathematical model; measurement; radiation physics; Radioactive beam; radioactivity; recording; Transient field